Plant closing ethics root in American law - Millspaugh, Peter E. (Journal of business ethics, 1990)
The harsh consequences of the American plant closing epidemic in recent years on workers, their families, and their communities, has raised widespread ethical and moral concerns. In the early 1970s, a diverse group of academics, social activists, public policy analysts, and special interest organizations developed a number of legislative proposals designed to restrict closings by law. The proposals encountered many formidable obstacles in an increasingly hostile free-market environment. The business community was itself moved to assume some of the burdens precipitated by closures either unilaterally or through collective bargaining. At the same time, powerful business interests tenaciously fought the enactment of mandatory closing restrictions into law. Nevertheless, through a prolonged and tortuous odyssey, the requirements of advanced notice and worker severence pay have now begun to root in law. Their success stands as evidence of a continuing American public policy receptivity to ethics-driven concerns.